Two "Wrongs" Making a "Right" - Shwayder, Keith R. (Journal of Accounting Research, 1973)
Solomon and others' have examined the relationship between the book yield on assets using conventional depreciation method and the cash-flow yield or internal rate of return of the assets. A substantial discrepancy between these two yields is often observed. Of course, if firms used the internal rate of return method of depreciation recommended by Anton2 and Reynolds,3 there would be no discrepancy between the expected book yield and the expected cash-flow yield. Unfortunately, these are practical and institutional considerations which often prevent the accountant from implementing an internal rate of return method of depreciation. Bierman4 and Shwayder5 (hereinafter referred to as the previous papers) explored the effect of price-level adjustments on the book rate of